Specific Sialoforms Required for the Immune Suppressive Activity of Human Soluble CD52 - Shathili, Abdulrahman M.; Bandala-Sanchez, Esther; John, Alan; Goddard-Borger, Ethan D.; Thaysen-Andersen, Morten; Everest-Dass, Arun V.; Adams, Timothy E.; Harrison, Leonard C.; Packer, Nicolle H. (Frontiers in Immunology, 2019)
Human CD52 is a small glycopeptide (12 amino acid residues) with one N-linked glycosylation site at Asn3 and several possible O-glycosylation serine/threonine sites. Soluble CD52 is released from the surface of activated T cells and initiates immunosuppression by first sequestering pro-inflammatory HMGB1 followed by binding to the inhibitory sialic acid-binding immunoglobulin-like lectin-10 (Siglec-10) receptor on activated T cells. Our analysis of native CD52 purified from human spleen confirmed extensive heterogeneity in N-glycosylation and the presence of multi-antennary sialylated N-glycans with abundant polyLacNAc extensions, together with mainly di-sialylated O-glycosylation type structures. We then aimed to define the glycan structures on recombinant soluble human CD52- immunoglobulin Fc fusion protein that correlate with its immune suppressive activity. Glycomics (porous graphitised carbon-ESI-MS/MS) and glycopeptide (C8-LC-ESI-MS) analysis after factor Xa-based Fc removal revealed that bioactive CD52 was characterised by a higher abundance of tetra-antennary α-2,3/6 sialylated N-glycans compared to less bioactive CD52. Moreover, the relative abundance of the α-2,3 sialic acid linkage correlated with higher bioactivity. Removal of α-2,3 sialylation abolished bioactivity, which was restored by re-sialylation with α-2,3 sialyltransferases. Bioactive glycoforms of CD52-Fc were isolated by fractionation on an anion exchange MonoQ-GL column. The CD52 component of fractionated bioactive CD52-Fc displayed mainly tetra-antennary α-2,3 sialylated N-glycan structures and decreased relative abundance of bisecting GlcNAc structures compared to non-bioactive adjacent fractions. In addition, O-glycan core type-2 di-sialylated structures at Ser12 were more abundant in bioactive CD52 fractions. These features describe the active glycoforms of CD52 that confer immunosuppressive activity of soluble CD52.